Low Grade Coal Quality With Up Graded Brown Coal Technology - Myson Myson (International Journal of Multidisciplinary Sciences and Arts, 2024)
The aim of this research is to increase the calorific value of coal. In this way, coal which has a calorific value of 3500 kCal/kg can be increased to 6500-7000 kCal/kg. Apart from that, by carrying out this up grading, a number of volatile meters will disappear as a result of the heating and pressure process. The knock-on impact is an increase in the economic value of coal and thus the selling price will be more competitive. After the data was collected, the data was analyzed using descriptive methods. The descriptive method is used to describe the upgraded brown coal (UBC) process. Findings that can be obtained in this research include: 1) Potential company profits can be increased, 2) Increased local government income through taxes, 3) Many mining areas can be exploited, 4) Reduction of unemployment by expanding employment opportunities in the mining sector, 5) Reducing environmental damage by mining power by mining wisely. 6) Reducing environmental pollution due to the combustion process. 7) With this process, investment in the coal mining sector can be increased. This research concludes that the economic value of low quality coal will increase and the profits that can be obtained will be better.